2013
DOI: 10.3141/2339-08
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Bicycle Traffic Patterns in Five North American Cities

Abstract: This study used a unique database of long-term bicycle counts from 38 locations in five North American cities and along the Route Verte in Quebec, Canada, to analyze bicycle ridership patterns. The cities in the study were Montreal, Quebec; Ottawa, Ontario; and Vancouver, British Columbia, in Canada and Portland, Oregon, and San Francisco, California, in the United States. Count data showed that the bicycle volume patterns at each location could be classified as utilitarian, mixed utilitarian, mixed recreation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 8 publications
3
62
0
3
Order By: Relevance
“…1c. The bikeshare trip distributions show a primary utilitarian pattern (Miranda-Moreno et al, 2013). It is consistent with the 2016 CaBi survey (LDA Consulting, 2016), where 65% of respondents confirmed that commuting was a primary trip purpose for their bikeshare usage.…”
Section: Data Analysis and Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…1c. The bikeshare trip distributions show a primary utilitarian pattern (Miranda-Moreno et al, 2013). It is consistent with the 2016 CaBi survey (LDA Consulting, 2016), where 65% of respondents confirmed that commuting was a primary trip purpose for their bikeshare usage.…”
Section: Data Analysis and Resultssupporting
confidence: 80%
“…7 shows the comparisons of the temporal distributions of hourly averaged trip counts between weekday and weekend by different types of trips and users respectively. Both the O-O trip users and casual users take more trips in weekend than in weekday, expressing a typical recreational pattern (Miranda-Moreno et al, 2013) as shown in Fig. 7a and Fig.…”
Section: Trip Purposementioning
confidence: 94%
See 1 more Smart Citation
“…In terms of time-based factoring and trip purposes, this study provides further evidence that the bicycle factor groupings developed by Miranda-Moreno et al (2013) later extended to mixed-mode trail traffic by Hankey et al ( 2014) generally are supported by the CycleTracks trip purpose responses. Researchers and practitioners are urged caution in the application of a potentially growing field of crowdsourced datasets, for they may or may not represent the given population that is considered in a transportation planning context.…”
Section: Resultssupporting
confidence: 51%
“…These efforts typically involve establishment of a set of permanent automated counters at a fixed number of locations believed to represent specific traffic patterns and then collection of a large number of short-duration (e.g., two to seven day) samples that can be used to characterize flows on a network. Statistics and ratios from the permanent sites are used to extrapolate the sample counts and obtain estimates of daily traffic (Federal Highway Administration, 2013;El Esawey, Lim, Sayed, & Mosa, 2013;Miranda-Moreno, Nosal, Schneider, & Proulx, 2013;Nordback, Marshall, Janson, & Stolz, 2013;Hankey, Lindsey, & Marshall, 2014). Several studies of trail use using these technologies and monitoring approaches have been reported (e.g., Lindsey, Wilson, Rubchinskaya, Yang, & Han, 2007;Wang, Lindsey, Hankey, & Hoff, 2014).…”
Section: Background and Literature Reviewmentioning
confidence: 99%